Zamenjava / ukinjanje terapije s psihofarmaki - Banović, Ana (Farmacevtski vestnik, 2015)
This article presents a clinical case with optimization of drug treatment. In a psychiatric hospital we can rarely see a patient with one psychotropic drug, although we know that effective monotherapy has advantages over polipharmacotherapy. The concomitant use of several drugs acting on central nervous system can bring more risks than benefits for the patient. Before adding another drug we should exclude adverse drug reactions as the cause of new onset of symptoms. With appropriate knowledge and participation in the health team, a clinical pharmacist can significantly contribute to solving complications with medication. This case can be a good stimulation for a better cooperation between a psychiatrist in a hospital, a psychiatrist in asocial care institution and a clinical pharmacist.
Keywords: psihofarmaki; neželeni učinki; klinični farmacevti; optimizacija zdravljenja z zdravili